114 The relationship of cell mediated immune response of Brahman cows on calving interval. (29th July 2019) - Mund, Marianna E; Neuendorff, Don A; Quail, Lacey; Banta, Jason P; Riley, David G; Welsh, Thomas H; Randel, Ronald D
Abstract: The relationships between cell-mediated immune response (CMIR) of cows and calving interval and calf growth were evaluated. Calving interval was evaluated for each of the initial 7 life-time opportunities that females had to produce a calf. The number of days from when the cow had a calf until she calved again determined the cow's calving interval for each year. The Spring breeding seasons were divided into 45-d artificial insemination and 45-d natural service periods. The Fall breeding season was natural service each year. Multiparous Brahman cows (n = 435) had records for breeding and calving dates and calf weaning weights. The CMIR (hypersensitivity response to Candida albicans measured using tail-fold thickness) was determined once for each female in the Fall and early Winter 2015. Cows were classified into response groups based on mean and SD of CMIR. High responders were those with CMIR ½ SD ≥ the mean (≥ 2.8 mm), Intermediate cows were within ½ SD of the mean (2.7-1.8 mm), and cows ½ SD ≤ the mean were Low (≤ 1.7 mm). Data were analyzed using repeated measures, mixed, and Chi Square procedures (SAS 9.4). Variables included calving interval, cow age, CMIR response group, pregnancy status, calf count, calf sex, cow sire, calf sire, and calf adjusted 180-d weaning weight. A greater proportion of High CMIR cows made it to their 6th calving interval. Chi Square analysis indicated that High CMIR cows were more likely to remain in the herd longer and produce a calf each year. Cows with High CMIR had a greater stayability (P = 0.1). Selection for High CMIR can result in selection of cows which are more likely to remain in the herd long enough to be profitable as they have a greater stayability and shorter calving intervals (about 25 days) than their Low CMIR herdmates.